2017
DOI: 10.1002/jaal.682
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Emotive Empathy With Informational Text: Three Students’ Think‐Aloud Protocols ofGettysburg: The Graphic Novel

Abstract: Although the popularity and use of graphic novels in literacy instruction has increased in the last decade, few sustained analyses have examined adolescents’ reading processes with informational texts in social studies classrooms. Recent research that has foregrounded visual, emotional, and embodied textual responses situates this qualitative study, in which three eighth‐grade students learned about the graphic novel format, responded in writing to interpretive prompts, and thought aloud during their reading o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
(18 reference statements)
2
22
0
5
Order By: Relevance
“…Interestingly, Chisholm, Shelton, and Sheffield () recently reported on a study in which eighth‐grade students read an informational graphic novel in a social studies class. Using strategies requiring students to adopt the perspective of a character in the novel, the researchers concluded that the visual images, more than written dialogue in the text, prompted students’ emotional empathy.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Interestingly, Chisholm, Shelton, and Sheffield () recently reported on a study in which eighth‐grade students read an informational graphic novel in a social studies class. Using strategies requiring students to adopt the perspective of a character in the novel, the researchers concluded that the visual images, more than written dialogue in the text, prompted students’ emotional empathy.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This demonstrates the power of multimodality-through physically seeing the image, the reader was able to empathize with a nameless character. 10 Having readers create their own graphic novels allows "increased critical thinking [that] comes into play when students are asked to create a comic book that does not just require them to regurgitate information about a story or time in history, but to reflect on the story." 11 For historical graphic novels, prompts can include to tell a different ending, to portray the story from one actor's point of view or to think about how events would be different in modern times.…”
mentioning
confidence: 99%
“…For example, compared with The Rabbits, an informational text such as Gettysburg: The Graphic Novel gives an uncomplicated account of a well-known historical event. Nevertheless, it can still convey novel insights beyond the scope of a textual account (Chisholm et al 2017). More importantly, regardless of whether the stimulus book offers few or many discussion opportunities, a teacher aiming to encourage sophisticated levels of historical awareness in a classroom will need to be strategic about the type of thought problems that students contemplate.…”
mentioning
confidence: 99%
“…First, they enhance readability. A common misconception among teachers is that picture books are most suitable for struggling readers (Chisholm et al 2017, p. 289). However, Youngs' (2012 studies showed that all students, struggling or not, gain additional meaning from imagery.…”
mentioning
confidence: 99%